Deconstructing “The Other”: Female Resistance In Great Expectations Through Simone De Beauvoir’s Lens - Yollanda Aprila Nirwana; Ruly Indra Darmawan (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The researchers used this research to identify the forms of resistance and subordination exhibited by female characters. The research utilized a descriptive, qualitative, and feminist approach, focusing on Simone de Beauvoir's concept of Otherness in The Second Sex. Data was gathered by carefully reading and observing Great Expectations by Charles Dickens, including narration, monologue, and character behaviors. Furthermore, the researchers determined that female characters (Estella, Miss Havisham, and Biddy) lose their subjectivity as a result of the subordination of women and societal expectations that required them to conform to traditional norms in the Victorian era. Women are defined as "other" rather than autonomous beings who stand alone, according to Beauvoir's idea of subordination. Therefore, as a form of resistance in Beauvoir's concept, female characters must conduct transcendence to pursue freedom to erase their Otherness. The resistance is found using Beauvoir's concept theory of women's existence. The concept is divided into three main points: women's intellect, being themselves, and concretizing themselves—the result of resistance shaped in the form of dialogue or narration in the novel. Additionally, the researchers use this research to gather relevant information for future studies and develop feminist analyses.